2019
DOI: 10.1177/1071181319631108
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Natural Language Processing in Procedure Design

Abstract: Procedures play a vital role in high-risk systems in ensuring that the required level of system performance is achieved while maintaining the associated risks below an acceptable level. An effective procedure has a low level of task complexities i.e., elements contributing to a multiplicity of paths/outcomes, uncertainty in information, interdependency, a multiplicity of instructions/object of instructions and an excess amount of information. As a part of this study, we have developed a Natural Language Proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Some studies have found that less experienced people benefit from a version with more detailed steps in a procedure and more experienced people from a shorter version. 18 Indeed, some evidence shows that those with more experience are more likely to make an error if there are more words in the step of a procedure. 44 It is important to note that these findings are preliminary in nature, and important information regarding this idea is still not known.…”
Section: ■ Creating a Standard Operating Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have found that less experienced people benefit from a version with more detailed steps in a procedure and more experienced people from a shorter version. 18 Indeed, some evidence shows that those with more experience are more likely to make an error if there are more words in the step of a procedure. 44 It is important to note that these findings are preliminary in nature, and important information regarding this idea is still not known.…”
Section: ■ Creating a Standard Operating Proceduresmentioning
confidence: 99%
“…The lack of direct guidance regarding how to produce laboratory SOPs illustrates a gap in lab safety and effectiveness. Indeed, Franz suggests that, of the three pillars for safe and effective laboratory operations (i.e., facilities, equipment, and procedures), the procedures pillar is the most critical and most likely one to fail. , …”
Section: The Need For Effective Proceduresmentioning
confidence: 99%
See 3 more Smart Citations